The Use and Misuse of Information in Securitate’s Files: The Case of Plamadeala - Plamadeala, Cristina (Eurostudia, 2015)
This short article discusses a series of Securitate documents which contain various inconsistencies, and which were written on or about the Romanian theologian Antonie Plamadeala. Examining these files, I attempt to reconstruct the case Securitate built against Plamadeala in the late 1940s, and point to errors and forgeries, which they may contain. Stated differently, I look at evidence, which may have been fabricated by Securitate in order to prove Plamadeala’s alleged ties to the Legionary Movement. I do this by first laying out the series of accusations the Romanian secret police brought against Plamadeala in 1949 and the way in which it constructed its evidence to support its case against him. I then offer a succinct analysis of ways in which one may derive truth from the plethora of information such files may bring to the attention of the modern investigator, truth which, as this article shows, is often juxtaposed with untruth in Securitate archival records.